Effects of chronic ascariasis and trichuriasis on cytokine production and gene expression in human blood: a cross-sectional study. - Miguel Reina Ortiz; Fernanda Schreiber; Susana Benitez; Nely Broncano; Martha E Chico; Maritza Vaca; Neal Alexander; David J Lewis; Gordon Dougan; Philip J Cooper (Public Library of Science (PLoS), 2011)
Chronic soil-transmitted helminth (STH) infections are associated with effects on systemic immune responses that could be caused by alterations in immune homeostasis. To investigate this, we measured the impact in children of STH infections on cytokine responses and gene expression in unstimulated blood.Sixty children were classified as having chronic, light, or no STH infections. Peripheral blood mononuclear cells were cultured in medium for 5 days to measure cytokine accumulation. RNA was isolated from peripheral blood and gene expression analysed using microarrays. Different infection groups were compared for the purpose of analysis: STH infection (combined chronic and light vs. uninfected groups) and chronic STH infection (chronic vs. combined light and uninfected groups). The chronic STH infection effect was associated with elevated production of GM-CSF (P=0.007), IL-2 (P=0.03), IL-5 (P=0.01), and IL-10 (P=0.01). Data reduction suggested that chronic infections were primarily associated with an immune phenotype characterized by elevated IL-5 and IL-10, typical of a modified Th2-like response. Chronic STH infections were associated with the up-regulation of genes associated with immune homeostasis (IDO, P=0.03; CCL23, P=0.008, HRK, P=0.005), down-regulation of microRNA hsa-let-7d (P=0.01) and differential regulation of several genes associated with granulocyte-mediated inflammation (IL-8, down-regulated, P=0.0002; RNASE2, up-regulated, P=0.009; RNASE3, up-regulated, p=0.03).Chronic STH infections were associated with a cytokine response indicative of a modified Th2 response. There was evidence that STH infections were associated with a pattern of gene expression suggestive of the induction of homeostatic mechanisms, the differential expression of several inflammatory genes and the down-regulation of microRNA has-let-7d. Effects on immune homeostasis and the development of a modified Th2 immune response during chronic STH infections could explain the systemic immunologic effects that have been associated with these infections such as impaired immune responses to vaccines and the suppression of inflammatory diseases.